Secular Slowing of Auditory Simple Reaction Time in Sweden (1959–1985) - Madison, Guy; Woodley of Menie, Michael A.; Sänger, Justus (Frontiers in Human Neuroscience, 2016)
There are indications that simple reaction time might have slowed in Western countries, based on both cohort- and multi-study comparisons. A possible limitation of the latter method in particular is measurement error stemming from methods variance, which results from the fact that instruments and experimental conditions change over time and between studies. We therefore set out to measure the simple auditory reaction time (SRT) of 7,081 individuals (2,997 males and 4,084 females) born in Sweden 1959-1985 (subjects were aged between 27 and 54 years at time of measurement). Depending on cut-offs and adjustment for ageing related slowing on SRT, the data suggest that SRT has increased between 3 and 16 ms in the 27 birth years covered in the present sample. The slowing is unlikely to be explained by attrition, as evaluated by comparing the general intelligence × birth-year interactions and standard deviations for both male participants and dropouts, utilizing military conscript cognitive ability data. The present result is consistent with previous studies employing alternative methods, and may result from several synergistic factors, such as possible recent micro-evolutionary trends favouring lower g in Sweden and the effects of industrially produced neurotoxic substances on peripheral nerve conduction velocity.